Behavioral Aspects of Budgeting: A Perspective on Leadership Values in the Bhisma Parwa - I Putu Bagus Satria Wibawa (Publikasi Indonesia, 2026)
Budgeting is not merely a technical and numerical process; it is deeply intertwined with human behavior, values, and leadership. However, dysfunctional behaviors such as budgetary slack often arise when budgets are imposed rigidly without considering ethical and cultural dimensions. The purpose of this article is to reflect the value of leadership in Bhisma Parwa in looking at the behavioral aspects of budgeting. This article used an interpretive review method with a qualitative approach and data obtained from literature studies. The value of leadership in Bhisma Parwa is used in assessing the budgeting process. The budgeting process is closely related to the leadership values in Bhisma Parwa. Leaders need value to direct employee behavior as the party that will realize the budget. Bhisma Parwa is used to pursue a fair budgeting process. The budgeting process requires values, leaders, and systems. The value of leadership in Bhisma Parwa can be a solution so that organizational leaders can develop a budgeting system that triggers positive employee performance. This article demonstrates the use of leadership values in Bhisma Parwa in looking at behavioral aspects of the budgeting process that have not been used before.